Randomized, controlled, proof‐of‐concept trial of MK‐7622 in Alzheimer's disease. Issue 1 (26th April 2018) - Voss, Tiffini; Li, Jerry; Cummings, Jeffrey; Farlow, Martin; Assaid, Christopher; Froman, Samar; Leibensperger, Heather; Snow‐Adami, Linda; McMahon, Kerry Budd; Egan, Michael; Michelson, David
Abstract: Introduction: We evaluated the selective M1 muscarinic positive allosteric modulator, MK‐7622, as adjunctive cognitive enhancing therapy in individuals with Alzheimer's disease. Methods: A randomized, double‐blind, proof‐of‐concept trial was performed. Participants with mild‐to‐moderate Alzheimer's disease, being treated with an acetylcholinesterase inhibitor, were randomized 1:1 to 45 mg of MK‐7622 or placebo for 24 weeks. Endpoints included the mean change from baseline in Alzheimer's Disease Assessment Scale–Cognitive Subscale (ADAS‐Cog11 ) at 12 weeks and Alzheimer's Disease Cooperative Study–Activities of Daily Living Inventory at 24 weeks. Results: Two hundred forty participants were randomized. The trial was stopped for futility after meeting prospectively defined stopping criteria. MK‐7622 did not improve cognition at 12 weeks (group difference in ADAS‐Cog11 : 0.18 [95% confidence interval: −1.0 to 1.3]) or function at 24 weeks (group difference in Alzheimer's Disease Cooperative Study–Activities of Daily Living Inventory: 0.06 [95% confidence interval: −2.4 to 2.5]). More participants taking MK‐7622 discontinued study medication because of adverse events than those taking placebo (16% vs 6%) and who experienced cholinergically related adverse events (21% vs 8%). Discussion: MK‐7622 (45 mg) does not improve cognition or function when used as adjunctive therapy in mild‐to‐moderate Alzheimer's disease. Highlights: MK‐7622 is a positive allosteric modulator of the M1 receptor. MK‐7622 did not improve cognition or function in Alzheimer's disease patients. MK‐7622 increased cholinergically related side effects in Alzheimer's disease patients. M1 positive allosteric modulation is not useful for treating Alzheimer's disease.